Gambaran Kesehatan dan Sosial Ekonomi Calon Pengantin Putri pada Pelaku Perkawinan Anak di Kabupaten Lamongan - Rery - Afianto; Srimarti Rukmini Devy; Riska Oktaviana; Nur Ilmya Nugraha Ningrum Irfandi Putri (Poltekkes Kemenkes Padang, 2024)
In 2023, the Religious Court of Surabaya recorded 307 marriage dispensations, with the health of female prospective brides and socioeconomic issues as the main factors in preventing child marriage in Lamongan Regency. This study aims to identify the health and socioeconomic conditions of female prospective brides involved in child marriage. The research employed a descriptive method, utilizing secondary data from a screening report of prospective brides in Lamongan Regency conducted in May 2023 by the Stunting Reduction Acceleration Team. The sample consisted of 38 female prospective brides from four sub-districts with the highest rates of child marriage. Data analysis was performed descriptively, using Microsoft Excel for data processing and presentation in tabular form. The results showed that 36.8% of respondents had a Body Mass Index (BMI) below 18.5, 36.8% had Mid-Upper Arm Circumference (MUAC) below 23.5, and 31.6% experienced anemia. Although 23.7% came from poor families, 73.3% of child marriage perpetrators were from financially capable families. In conclusion, despite health issues, most child marriage perpetrators do not come from underprivileged families, highlighting the importance of nutritional improvement and health awareness for female prospective brides.